Research on flow field reconstruction of complex fault-block reservoir during ultra-high water cut period - Yunpeng Li; Dongcheng Liu; Liang Zhao; Rui Wang; Hui Xu; Lu Liu; Zhuxin Zhang; Risu Hu; Donglin Wang; Yang Si (Discover Applied Sciences)
Abstract Complex fault block reservoirs are usually characterized by irregular boundary and small area, so it is difficult to arrange regular injection-production well pattern. At the same time, due to the strong heterogeneity of the reservoir, the horizontal and vertical waterflood sweep is uneven. Although entering the ultra-high water cut period, there is still abundant remaining oil in some areas, and it is necessary to reconstruct the flow field to further improve the swept efficiency of water drive, so as to improve the recovery efficiency. Considering the contradiction between plane and water injection comprehensively, the standard deviation of movable movable geological reserves, the average value of movable movable saturation, the standard deviation of water drive index and the average value of water drive index were selected to construct the standard for the flow field reconstruction measures of complex fault blocks, and the flow field reconstruction measures of different fault blocks were defined. The prediction results show that the ineffective water cycle is improved and the water drive recovery rate is increased by 3.1%.